Knowledge of danger signals of pregnancy among clients of maternal health services in tertiary care teaching hospital, Pune - Kumar, Arunesh; Gupta, Sachin; Pore, Prasad (Asian Journal of Medical Sciences, 2021)
Background: India is among countries with a high maternal mortality rate. Every pregnant woman is at risk of developing pregnancy-related complication. It is not understood if and how the information and education on danger signals of pregnancy; translates into appropriate actions when a woman experiences a danger signal. Knowledge and recognition of danger signals during pregnancy would result in timely emergency obstetric care. Aims and Objectives: This study aims to determine the knowledge of key danger signals of pregnancy and its associated factors among the clients of maternal health services in tertiary care teaching hospital, Pune. Materials and Methods: This was a cross-sectional study conducted in obs. and gyne. dept. of tertiary care hospital for a period of 1 month that enrolled 55 eligible women who attended ANC and PNC clinic within study period. Ethical approval for the study was obtained from the IEC. The women were interviewed using a pre-tested questionnaire. All the women attending ANC and PNC clinic with a minimum of four ANC visits qualified the women for the inclusion in the study. Data analysis was performed using SPSS Version 20. The analyzed data were presented in suitable tabular format. Results: Out of 55 mothers, 43.6% know about four or more danger signals whereas 56.4% have knowledge of <4. The most recalled danger signals by the clients was labor pain before 8 months (70.9%), while no one is aware about the danger signal failure of placenta to come out (0%). Conclusion: This study indicated that the knowledge level of women regarding danger signals of pregnancy was low and affected by education level. Therefore, the identified deficiencies in awareness should be addressed through maternal and child health services.